ANALISIS JALUR SUKU BUNGA DAN KREDIT DALAM TRANSMISI KEBIJAKAN MONETER DI INDONESIA - Sukma Ria Alafanta; Doni Satria (Universitas Negeri Padang, 2026)
This study aims to analyze the monetary policy transmission mechanism inIndonesia through interest rate and credit channels, and evaluate theireffectiveness and response speed toward real output and inflation for the 2017–2024 period. The research method used is quantitative with a VectorAutoregression (VAR) or Vector Error Correction Model (VECM) approach tocapture dynamic relationships and long-term linkages between variables. Thetested variables include BI7DRR, money market interest rates, credit interestrates, credit volume, Industrial Production Index (IPI), and inflation. The resultsshow a cointegration relationship that validates the error correction mechanismtoward long-term equilibrium. Both channels significantly transmit monetarypolicy signals to the real sector, although an incomplete interest rate pass-through remains in credit rates. The study concludes that both channels playvital roles in affecting aggregate demand, with their effectiveness depending onthe banking sector's adjustment speed. Bank Indonesia is advised to strengthenpolicy coordination to minimize transmission barriers, ensuring price stabilityand sustainable economic growth.